The association between quality of life(QOL) and health literacy among junior middle school students: a cross-sectional study - Min Ran; Linli Peng; Qin Liu; Michelle Pender; Fang He; Hong Wang (BMC, 2018)
Abstract Background Lower health literacy is associated with poor quality of life (QOL) among patients with chronic disease; little is known about this relationship among the general population, especially for child and adolescent. To fill this gap, this paper aimed to investigate the association between health literacy and QOL in junior middle school students, and explore how QOL varies by health literacy. Methods An anonymous cross-sectional survey was conducted among junior middle school students (aged 12-15) from Shapingba district, Chongqing in China, and participants were recruited using stratified cluster sampling. Health literacy and QOL were measured using two validated scales, and quantified using a five-point Likert scale with health literacy classified as low, medium, or high. We used multivariable logistic regression to test adjusted association between health literacy and QOL. Results A total of 1774 junior middle school students were evaluated, with the mean age was 13.8 ± 1.0 and of whom 905 (51.0%) were male. About 25.5% of the research subjects had a low health literacy. When controlling for age, grade, family structure and other covariates, highest discrimination was found among participants with low to high health literacy. Overall, Students who equipped with higher health literacy was associated with greater QOL (P < 0.01), and this discrimination remained significant in subscales: physiological well-being (P < 0.01), mental well-being (P < 0.01), social well-being (P < 0.01) and pubertal well-being (P < 0.01). Conclusions The prevalence of low health literacy among junior middle school students in Chongqing area was relatively high, and inadequate health literacy may contribute to poorer QOL among junior middle school students. It merits further longitudinal studies to confirm the impact of health literacy on QOL. Overall, to improve students' QOL, public health efforts for further improving awareness and enhancing effective promotion and education are urgently needed in junior middle school students, especially for low health literacy populations.